1996
DOI: 10.1002/ana.410400305
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced Parkinson's disease by posterior GPi pallidotomy: 1‐year results of a pilot study

Abstract: The effects of posterior internal pallidal ablation (GPi pallidotomy) on parkinsonian signs and symptoms were studied in 15 patients with medically intractable Parkinson's disease (PD). The sensorimotor territory of the internal portion of the globus pallidus and the adjacent optic tract and internal capsule were identified with microelectrode recording and stimulation. Radiofrequency lesions were then created in the identified sensorimotor territory. Pallidotomy significantly improved all cardinal parkinsonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
288
2
10

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 520 publications
(326 citation statements)
references
References 26 publications
24
288
2
10
Order By: Relevance
“…The UPDRS (Part IIImotor score) was used because it allows data comparisons between different studies, as it is a widely used scale. The mean UPDRS score was lower after PVP, which is in accordance with the literature 5,11,14 . The different studies that reported neurological evaluations in the off and on phase observed an improvement only in the off phase 5,11,[14][15][16] .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The UPDRS (Part IIImotor score) was used because it allows data comparisons between different studies, as it is a widely used scale. The mean UPDRS score was lower after PVP, which is in accordance with the literature 5,11,14 . The different studies that reported neurological evaluations in the off and on phase observed an improvement only in the off phase 5,11,[14][15][16] .…”
Section: Discussionsupporting
confidence: 92%
“…The mean UPDRS score was lower after PVP, which is in accordance with the literature 5,11,14 . The different studies that reported neurological evaluations in the off and on phase observed an improvement only in the off phase 5,11,[14][15][16] . Ondo et al 14 speculated that the improvement in the off phase is consistent with the traditional model of the basal ganglia physiology in PD, which determines the presence of tonic thalamic hypo activity resulting from the excessive inhibition induced by the internal palladium.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Estes resultados assemelham-se aos de outros estudos realizados, em que também não houve mudança estatisticamente significante na dose de levodopa 3,4,6,16,[26][27][28] . Na análise realizada por Masterman et al, que avaliaram pacientes parkinsonianos submetidos a palidotomia unilateral no 3º e 6º mês pós-operatório, 44% dos pacientes mantiveram a mesma dose de levodopa, 41% tiveram a dose diminuída e 15% necessitaram de aumento na dose de levodopa 5 .…”
Section: Discussionunclassified